2012
DOI: 10.1177/1052562912446067
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Cold-Calling on Student Voluntary Participation

Abstract: Classroom discussion is perhaps the most frequently used “active learning” strategy. However, instructors are often concerned about students who are less inclined to participate voluntarily. They worry that students not involved in the discussion might have lower quality learning experiences. Although instructors might consider whether to call on a student whose hand is not raised (“cold-call”), some instructors resist cold-calling fearing that the student will feel uncomfortable. This study examines the impac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
60
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(63 citation statements)
references
References 24 publications
2
60
1
Order By: Relevance
“…We did not observe an increase in total volunteer rates after exposure to Cold Call, as had been previously reported (E. J. Dallimore, Hertenstein, and Platt 2012). However, we did find that students became more likely to initiate contact with their GTA during group work time as the term progressed.…”
Section: Discussionsupporting
confidence: 82%
“…We did not observe an increase in total volunteer rates after exposure to Cold Call, as had been previously reported (E. J. Dallimore, Hertenstein, and Platt 2012). However, we did find that students became more likely to initiate contact with their GTA during group work time as the term progressed.…”
Section: Discussionsupporting
confidence: 82%
“…Cold calling effectively flips the class, because students come to class prepared and they actively reinforce in class what they have already studied (Gross et al ., 2015; Jensen et al ., 2015). Cold calling, on groups or individuals, is a very effective method of ensuring that students not only read before class but also make an effort to understand what they read (Dallimore et al ., 2012). Holding students accountable each class facilitates students’ construction of their own knowledge, which is how people learn best (NRC, 2000; Tanner, 2009; Moravec et al ., 2010; Smith et al ., 2011b; Freeman et al ., 2014).…”
Section: Pedagogymentioning
confidence: 99%
“…Peng, 2012;Hsieh, 2014) -while a sufficient condition for receiving a high score for participation -is not a necessary condition. Alongside the ten criteria adopted in Table 1, previous research suggests participation rates increase when a participation score is included in the assessment rubric (Dallimore et al 2004(Dallimore et al , 2013Carstens et al 2012). Dallimore et al (2004) found students' level of participation increased when participation was overtly included as part of the grading criteria, while Dallimore et al (2013) found an increase in the participation of those who were randomly called upon to participate in in-class discussions, constituting an element of 'surprise'.…”
Section: Classroom Participationmentioning
confidence: 99%
“…Alongside the ten criteria adopted in Table 1, previous research suggests participation rates increase when a participation score is included in the assessment rubric (Dallimore et al 2004(Dallimore et al , 2013Carstens et al 2012). Dallimore et al (2004) found students' level of participation increased when participation was overtly included as part of the grading criteria, while Dallimore et al (2013) found an increase in the participation of those who were randomly called upon to participate in in-class discussions, constituting an element of 'surprise'. We also note that in certain EFL curricula types (such as task-based curricula),-participation in the tasks themselves is the focus of the total course assessment, yet these curricula lay outside of the scope of this paper.…”
Section: Classroom Participationmentioning
confidence: 99%